Practical Guide for Determining the Reaction Rate and Reaction Order Based on the Colorimeter® Application - Azwa Fadilla Wafiq; Husna Amalya Melati; Erlina; Hairida; Masriani; Risya Sasri (Jurnal Pendidikan Kimia Indonesia, 2022)
The practical activities needed in chemistry lessons. However, during the covid-19 pandemic, a suitable practical guide is needed. Therefore, a practical guide that can involve students directly in practical activities in online learning and blended learning is needed. The purpose of this study is to determine the feasibility of the Practical Guide for Determining Reaction Rate and Reaction Order Based on the Colorimeter® Application based on expert judgement and students’ response. This study employs a research and development (R&D) using 4D(Four-D) model, starting from define, design, develop, and dissemination stages. This research is limited to the develop stage due to the limited time and ability of the researcher. The subject of this study was a practical guide which was tested to 6 students in the initial trial and 20 students of Chemistry Education FKIP Untan in the main trial. Data collection tools used are the feasibility assessment sheets and students’ response questionnaires. The results of expert assessment using the Gregory test closeness model indicate a very feasible criteria with the validity value of 1.00 which in a very high level in terms of the feasibility of the content, language, and graphics. The result of the initial trial and main trial obtained an average percentage of 91% and 94% respectively with very good criteria. The results of this study imply that the practical guide developed is suitable for use in the practical activities. In addition, the practical guide has an attractive appearance and can be used in practical activities to support students’ understanding of reaction rates’ concepts.